Optimalisasi Pengelolaan SDM Pondok Pesantren : Tantangan dan Solusi - Ipnu Nawawi , Riswandha; Elistatia , Usi; Hadiati, Eti; Junaidah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Pondok Modern Darussalam Gontor is a well-known Islamic boarding school that applies a distinctive human resource (HR) development model rooted in moral values and internal leadership training. As educational management becomes increasingly complex, optimizing HR presents specific challenges for Gontor. This study aims to explore how Gontor develops and manages its human resources while identifying key challenges and the strategies used to address them. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that Gontor’s internal cadre system, value-driven work culture based on sincerity (ikhlas), and strong alumni support serve as pillars of its HR system. The challenges identified include leadership regeneration, technological adaptation, and work-related fatigue. Solutions include continuous training, administrative digitalization, and early-stage commitment building. These insights offer valuable lessons for value-based educational institutions seeking to develop sustainable HR systems without reliance on financial incentives.